Political Handbook of the World 2022-2023: Revised and Updated Edition - Lansford, Tom (Washington D.C. : CQ Press, 2023)
The Political Handbook of the World provides timely, thorough, and accurate political information, with more in-depth coverage of current political controversies than any other reference guide. The updated 2022-2023 edition will continue to be the most authoritative source for finding complete facts and analysis on each country's governmental and political makeup. Compiling in one place more than 200 entries on countries and territories throughout the world, this volume is renowned for its extensive coverage of all major and minor political parties and groups in each political system. It also provides names of key ambassadors and international memberships of each country, plus detailed profiles of more than 30 intergovernmental organizations and UN agencies. And this update will aim to include coverage of current events, issues, crises, and controversies from the course of the last two years.
Description based on XML content.
Keywords: Comparative Politics (general); Elections & Political Campaigns; General Politics & International Relations